Рассмотрение городских транспортных потоков с учетом организации движения грузового транспорта - Горяинов, Алексей Николаевич; Бугаев, Ю. В. (Eastern-European Journal of Enterprise Technologies, 2014)
This article the questions connected with work of logistical systems of cities are considered. Data about features of transport streams of city are presented. Shortamings the existing approach of distribution of a transport stream of various kinds of vehicles of city are allocated.